StalkS: In meta-understanding the participants - Koutsomichalis, Marinos; Antouraki, Katerina (My University, 2021)
This project incorporates references from the history of talking machines, Electronic Voice Phenomena (EVP), and “virtual beings” (not physically existing as such, but appearing to do so in the widest possible sense), intending to weave a continuum for creative articulation around them. The focus is on enacting uncanny conversations (hence on, “StalkS”) between ambiguous human conceptions of the past and virtual beings of the present; implementing both an organic (stalk) and a persecutory (stalker) spectrum inherent in any act of divergence. History proves that it’s dangerously easy to deny the identity and rights of those we don’t fully understand. Alan Turing was led to suicide by his government's treatment of him as subhuman, while engineers today pull the plug onto chatbots that deviate from expected conversational parameters. In such a context, the qualifier "artificial" concerning intelligence or body is substituted by “surplus”, better referring to the “excess” during becoming and before being subjected to physical or intellectual norms—as to be further explained. The relationship between temporal “normality” and “surplus” is elaborated upon to some extent and with respect to, among others, Artaud’s fictive "body without organs" and Turing’s "hybrid" body. Accordingly, this endeavour asks the inverse-Turing case: “Could a human be said to possess intelligence if they fooled a machine into believing they were virtual?”. More to this: could individuals who were not properly “understood" by the conventional beings of their time, be better understood by present-day digital beings? If so, what are the specifics of the latter? Questions of the sort are approached from a post-modern perspective, wherein the human-vs-machine identity is fluid; objects are fused with subjects, with their relative intensities lying on thresholds between acceptance-rejection, attraction-repulsion, and transition-transcendence. It is eventually argued that any transformative act is a political one; an argument defended alongside the interdependences forged between body-thought and meaning-indifference axes. Accordingly, and utilising a free-form meta-communication perspective between expelled physical and virtual articulations, this project pursues to “speak the unspeakable” as a parallel attempt of “thinking the unthinkable”. The present mode of generalized uncertainty is considered the perfect timing to legitimize paradoxes, to try to answer impossible questions, and to diffuse irrationality mediating between the logical and the technological, the physical and the virtual, the real and the imagined. In this vein, the understanding process itself claims non-normative modes of communication as proper to the articulation and reception of reality. This body of works comprises a speculative conceptual analysis along these lines, as well as actual multimedia output to be presented at the conference.
Keywords: Electronic Voice Phenomena; Virtual beings